Synthesis and characterization of pure and cobalt doped magnesium oxide nanoparticles: Insight from experimental and theoretical investigation. (October 2018) - Obeid, Mohammed M.; Edrees, Shaker J.; Shukur, Majid M.
Abstract: Undoped and cobalt doped MgO nanoparticles (Mg1-x Cox O, x = 0, 0.03, 0.06 and 0.12) were prepared by co-precipitation method. The synthesized samples were characterized by using X-ray diffraction (XRD), differential thermal analysis (DTA) and Ultraviolet–Visible (UV–Vis) spectroscopy. The UV–Visible absorption spectra showed a redshift with the increase in cobalt doping content in MgO host lattice while corresponding bandgap energy of cobalt doped MgO-NPs was decreased with the increase of doping concentration. The XRD patterns revealed the formation of rock salt MgO phase nanostructures. The Rietveld analysis revealed the formation of impurity phase (Co3 O4 ), which was remarkably appear at higher doping concentration ( x = 0.12). Rietveld refinement was utilized to investigate the individual influences of coherent domain sizes and lattice strain on the peak broadening of the pure and cobalt doped MgO-NPs. The coherent domain size increased from 7.44 nm to 8.11 nm with increasing Co doping amount up to x = 0.06. The strain decreased with increasing in cobalt content. The decreasing trend in lattice constant " a " was observed with increasing doping concentration which confirms the incorporation of Co ions into the MgO host lattice. Furthermore, the linear and planar defects were also considered. First-principles calculations based on DFT were employed to determine elastic constants for the pure and doped MgO. These values were then used in combination with X-ray diffraction data to measure stacking fault energies as a function of doping concentration. The results showed that the stacking fault energy decreased as the doping concentration increase. The formation enthalpy and bonding properties of the studied compounds were also inspected. Further, the magnetic features of Co monodoping and (Co, Mg or O vacancy) co-doping in MgO host lattice were studied. The results reveal that the studied compounds may have potential applications in spintronics and magnetic data storage. Highlights: Pure and Co doped MgO nanoparticles were obtained using a simple co-precipitation method. The synthesized products were characterized by using XRD, UV–Vis, and DTA. Ab-initio analysis was used to evaluate the magnetic and elastic properties of the studied compounds. Ab-initio data was used in combination with XRD data to study the effect of doping on microstructural properties.